Fast nonlinear region localisation for nonlinear dielectric spectroscopy of biological suspensions - Ruiz, Gabriel Alfredo (2013)
The nonlinear properties of biological suspensions have been previously presented as a bulk phenomenon without the influences of the electrodes. However, some authors have showed that the behaviour of a biological suspension is due to the nonlinear characteristics of the electrode–electrolyte interface (EEI), which is modulated by the presence of yeast cells. We have developed a method, complementary to the nonlinear dielectric spectroscopy (NLDS) which is used for the study of the behaviour of EEI with resting cell suspensions of Saccharomyces cerevisiae. The method allows researchers to detect simply and quickly the voltage and frequency ranges where the metabolic activity of yeasts is detectable. This method does not replace NLDS, and aims to reduce the time during which the electrodes are exposed to corrosion by high voltages. In this paper we applied AC overpotentials (10–630 mV) with frequencies in the range from 1 to 1000 Hz. Also, we measured current harmonic distortion produced by the nonlinearity of the interface. Changes in the transfer function were observed when yeast suspension was used. Apart from the nonlinear response typical of the EEI, we also observed the biological nonlinear behaviour. The changes in the transfer functions were assessed using the overlapping index which was defined in terms of the conditional probability. The methodology was contrasted favourably with Fourier analysis. This novel strategy has the advantages of simplicity, sensitivity, reproducibility and involves basic tools such as the usual measurement of current.